2015
DOI: 10.15381/rivep.v26i2.11091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de Ninfas de Linguatula serrata en Ganado Bovino en Camales de Lima, Perú

Abstract: RESUMENLa linguatulosis es una zoonosis causada por Linguatula serrata, parásito que puede afectar al hombre en su estadio ninfal y adulto, siendo los principales mecanismos de transmisión el contacto con el perro doméstico y la ingesta de vísceras infectadas mal cocidas de bovinos. El presente estudio tuvo como objetivo determinar la prevalencia, abundancia e intensidad media del estadio ninfal de L. serrata en ganglios linfáticos mesentéricos yeyuno-iliacos de reses beneficiadas en dos camales de la ciudad d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In Talca, Chile, Carrillo et al (2017) analysed bovine liver obtained at a slaughterhouse and described the macroscopic lesions compatible with Linguatulosis, which were afterwards etiologically confirmed by stereoscopy, obtaining a prevalence of 13.8% and 6,7% respectively. Castro et al (2015) indicated a 5.97% of prevalence in bovine lymph nodes. The diagnostic method of Linguatulosis in slaughterhouses relies on the macroscopic visualisation of compatible lesions with occasional identification of nymphs.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In Talca, Chile, Carrillo et al (2017) analysed bovine liver obtained at a slaughterhouse and described the macroscopic lesions compatible with Linguatulosis, which were afterwards etiologically confirmed by stereoscopy, obtaining a prevalence of 13.8% and 6,7% respectively. Castro et al (2015) indicated a 5.97% of prevalence in bovine lymph nodes. The diagnostic method of Linguatulosis in slaughterhouses relies on the macroscopic visualisation of compatible lesions with occasional identification of nymphs.…”
Section: Resultsmentioning
confidence: 95%
“…For the presumptive macroscopic diagnosis of visceral Linguatulosis, the liver capsule was inspected, and 15 longitudinal cuts were made in search of compatible lesions (Valenzuela et al 1995, Castro et al 2015, Carrillo et al 2017. The detected compatible lesions were extracted with a margin of surrounding normal hepatic tissue of approximately 0.5 cm, immersed in 10% formalin (v/v), labelled and sent to the laboratory for routine histological processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linguatulosis is non-notifiable disease in Chile, despite being considered as a zoonotic disease and having importance in public health. En los hospederos intermedios, el parásito forma nódulos de hasta 5 mm de diámetro en la superficie del órgano o en el parénquima (Castro et al, 2015). La ninfa de L. serrata es bastante parecida al parásito adulto en su morfología, pero de menor tamaño.…”
Section: Introductionunclassified